DIVERSION AS A LEGAL CONCEPT THAT IS EQUITABLE FOR CHILDREN IN INDONESIA - Abdurrakhman Alhakim (Universitas Islam Kadiri, 2022)
Indonesia is obliged to guarantee children's rights so that their lives can run normally. As a manifestation of the fulfillment of child protection, Indonesia has ratified the Convention on the Children's Rights. To fulfill this responsibility, the Indonesian Child Protection Law was regulated. This law provides several articles to fulfill children's rights without distinguishing ethnicity, religion, race, class, gender, culture and language, legal status, birth order, physical and mental condition, and be responsible for formulating and implementing policies in the field of child protection. Children are legal subjects and national assets. As part of the younger generation, children play a very strategic role as the nation's next generation. In Indonesia, children are the successors of the ideals of a nation's struggle. The urgency of protecting children's rights makes this research examine the problem-solving of children who commit crimes. Efforts to resolve children's problems in conflict with the law are part of the cluster of the Convention on the Children’s Right; it is called 'special protection'. The resolution of children's problems facing the law is still interesting to study today. Based on this condition, there is a need for appropriate case resolution for children. One of them is the application of restorative justice through the diversion system. This research will examine the issue critically and normatively, that diversion is a legal concept that is fair to children in Indonesia. For this reason, this legal research uses doctrinal research methods. This legal research aims to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced in this research.